The effects of poultry and unconditional cash transfers on livelihoods outcomes: Evidence from the SPIR midline survey - Leight, Jessica; Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Tambet, Heleene (International Food Policy Research Institute, 2020)
Recent policy debates have focused renewed international attention on poultry as an asset that is widely accessible to women and has low start-up costs, increasing its potential to have significant positive welfare effects for poor households in developing countries. In 2016, Bill Gates promoted investment in chickens as a development strategy that would meaningfully increase incomes for poor women.1 In response, Chris Blattman suggested that large cash grants of the kind provided by Give Directly (Haushofer and Shapiro 2016) may be more effective at enhancing outcomes, given heterogeneity in households’ needs and capacity to raise chickens.2 This learning brief reports on evidence from an ongoing impact evaluation of a complementary program to Ethiopia’s Productive Safety Net Program, Phase 4 (PSNP4), called SPIR (Strengthen PSNP4 Institutions and Resilience) in rural Ethiopia, in which a cross-randomization of interventions providing poultry and cash transfers allows us to generate evidence highly relevant to this debate. The SPIR Development Food Security Activity (DFSA) in Ethiopia is a five-year program (2016–2021) supporting implementation of the PSNP4 as well as complementary livelihood, nutrition, gender, and natural resource management activities intended to strengthen the program and expand its impacts. Under funding from USAID’s Office of Food for Peace (FFP) and in close collaboration with the Government of Ethiopia, World Vision leads implementation of the SPIR DFSA in partnership with the Organization for Rehabilitation and Development in Amhara (ORDA) and CARE. SPIR DFSA targets more than 500,000 PNSP clients in 15 of the most vulnerable woredas in Amhara and Oromia regions of Ethiopia. SPIR DFSA also incorporates a substantial learning agenda intended to use evidence to improve the design of the DFSA, provide feedback to strengthen its delivery, and draw lessons both for local gov-ernment and other national and international stakeholders. World Vision, ORDA, and CARE provide guidance on the implementation of the learning agenda. IFPRI leads the planning and execution of the learning agenda activities. This learning brief reports midline effects of two specific dimensions of SPIR programming, a poultry package and a one-time cash transfer randomized to women in particularly poor households, on a set of livelihood outcomes measured in the midline survey conducted between July and October 2019.